Molecular dynamic simulation analysis of SARS-CoV-2 spike mutations and evaluation of ACE2 from pets and wild animals for infection risk. (February 2022) - Chen, Ping; Wang, Jingfang; Xu, Xintian; Li, Yuping; Zhu, Yan; Li, Xuan; Li, Ming; Hao, Pei
Abstract: Coronavirus Disease 2019 (COVID-19) is an ongoing global health emergency that has caused tremendous stress and loss of life worldwide. The viral spike glycoprotein is a critical molecule mediating transmission of SARS-CoV-2 by interacting with human ACE2. However, through the course of the pandemics, there has not been a thorough analysis of the spike protein mutations, and on how these mutants influence the transmission of SARS-CoV-2. Besides, cases of SARS-CoV-2 infection among pets and wild animals have been reported, so the susceptibility of these animals requires great attention to investigate, as they may also link to the renewed question of a possible intermediate host for SARS-CoV-2 before it was transmitted to humans. With over 226, 000 SARS-CoV-2 sequences obtained, we found 1573 missense mutations in the spike gene, and 226 of them were within the receptor-binding domain (RBD) region that directly interacts with human ACE2. Modeling the interactions between SARS-CoV-2 spike mutants and ACE2 molecules showed that most of the 74 missense mutations in the RBD region of the interaction interface had little impact on spike binding to ACE2, whereas several within the spike RBD increased the binding affinity toward human ACE2 thus making the virus likely more contagious. On the other hand, modeling the interactions between animal ACE2 molecules and SARS-CoV-2 spike revealed that many pets and wild animals' ACE2 had a variable binding ability. Particularly, ACE2 of bamboo rat had stronger binding to SARS-CoV-2 spike protein, whereas that of mole, vole, Mus pahari, palm civet, and pangolin had a weaker binding compared to human ACE2. Our results provide structural insights into the impact on interactions of the SARS-CoV-2 spike mutants to human ACE2, and shed light on SARS-CoV-2 transmission in pets and wild animals, and possible clues to the intermediate host(s) for SARS-CoV-2.